Sikap Hamba Tuhan terhadap Jemaat yang Mudur dari Pelayanan - Kejar Hidup Laia (ILLUMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2020)
Becoming God's Servant is a special call from God. God's Servant is the call of the congregation to someone who is considered to have godliness in his faith and actions of daily life. Whereas the word "servant" in Greek doulos, is a slave, it means that the servant is bound. The task of God's Servant has an important role in the growth of the church. In the journey of ministry, it is not always smooth faced by the Lord's servants, there are congregations that are growing spiritually mature and there are also those who withdraw from the ministry even leaving the church looking for another church or pastor. God's servant must be disappointed and even feel like a failure in the ministry. The same thing happened to Jesus when His disciples left Him because of his harsh words in rebuking His disciples. How is the attitude of the servants of God in facing the church who resigned in the service in terms of John 6:60-71. After describing it in the discussion, it was found that Jesus' attitude toward the students was firm and caring and loving the students. So, the attitude of God's Servant to the church who left the ministry is to love, pray for, make as a fellow worker of God not an enemy. Thus, God's servants continue to serve with enthusiasm despite many challenges in the ministry. AbstrakMenjadi Hamba Tuhan merupakan panggilan khusus dari Allah. Hamba Tuhan adalah jemaat panggilan kepada seseorang yang dipandang memiliki kesalehan dalam imannya dan tindakan hidup sehari-hari. Sedangkan kata "hamba" dalam bahasa Yunani doulos, adalah budak, artinya adalah hamba yang terikat. Tugas Hamba Tuhan memiliki peran penting dalam pertumbuhan jemaat. Dalam perjalanan pelayanan yang dihadapi oleh hamba Tuhan tidak selalu mulus, ada jemaat yang semakin dewasa secara rohani dan ada juga jemaat yang mundur dari pelayanan bahkan meninggalkan gereja mencari gereja atau gembala yang lain. Hamba Tuhan pasti kecewa bahkan merasa gagal dalam pelayanan. Hal yang sama dialami oleh Yesus ketika para muridNya meninggalkan Dia karena perkataanya yang keras dalam menegur murid-muridNya. Bagaimana sikap hamba Tuhan dalam menghadapi jemaat yang mundur dalam pelayanan ditinjau dari Yohanes 6:60-71. Setelah diuraikan dalam pembahasan, maka ditemukan sikap Yesus menghadapi para murid yaitu tegas dan peduli serta mengasihi para murid. Jadi, sikap Hamba Tuhan kepada jemaat yang meninggalkan pelayanan adalah mengasihi, mendoakan, menjadikan sebagai kawan sekerja Allah bukan musuh. Dengan demikian hamba Tuhan tetap melayani dengan semangat sekalipun banyak tantangan dalam pelayanan.